A season to celebrate - Michaels, Fern; Michaels, Fern.; Pearce, Kate, 1963-; Kauffman, Donna; Oliveras, Priscilla (New York, NY : Zebra Books, published by Kensington Publishing Corp., 2018)
A Christmas homecoming: Former Air Force Pararescueman Kevin Matthews is back home in Texas, working at his family's Christmas tree farm while deciding his next move. Or maybe he won't move at all, if sparks keep flying with the town's new surgeon, Kate Stafford ...
An unexpected gift: Widower Billy Morgan wishes his grown children still needed him. Good thing his longtime friend, Bella, does. She's planning her son's Christmas wedding and Billy is happy to help. Along the way they just might discover their own occasion to celebrate ...
Christmas in Blue Hollow Falls: Attorney Moira Brogan expects her brother's Christmas wedding to be a peaceful affair. She doesn't expect to be cornered by an unwanted lothario, rescued by a gorgeous Aussie chef--or be swept off her feet by said chef. Nursing a broken heart, the last thing she wants is a new romance. But Hudson Walker has other ideas ...
Holiday home run: Event planner Julia Louisa Fernandez dreams of a life in Chicago. But her family in Puerto Rico expects her to take over the catering business. Former pro baseball player Ben Thomas knows what that's like--and when they meet, he might be the one to inspire a winning strategy, just in time for the holidays ...
Christmas homecoming / Fern Michaels -- Unexpected gift / Kate Pearce -- Christmas in Blue Hollow Falls / Donna Kauffman -- Holiday home run / Priscilla Oliveras.
Keywords: Christmas stories, American; Romance fiction, American; Christmas fiction; Romance fiction; Short stories; Electronic books